(3efXheGJ eNJdaI aj Gdabg hGdBOGHs - (3GdfLaj, , GdCYSe, MeO Hf Ydj Hf MSjf Hf eMeO, (B1233 (3g`s ((3MSf Hf Ydj GdMdHjs)
(3ChdgG (B:s
(3fMeOc Gddge jG ef TQYG OjfG Hg GdfHj Wg UOYG (B*** (3hef CHGf Mcej GdEfSGf MjG hejJG CMSf GdHjGf (B*** (3Ke GdUdGI JJdh MeOg Ydi fHj dG fHj HYOg (B...s
(3BNQgG (B:s
... (3hCaUd Gdbhe QajY GdTGf ceG bO GSJMHg GdcGTGfj (B*** (3jLeY eGA dcd WTJ hGMO dCLd LeY GdTed agh GdhGQO (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\297s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis